'You Say Tomatoes' – avoiding trustee liability for breach of duties of care in English and US style trust deeds. Issue 3 (13th March 2021) - O'Hagan, Patrick
Abstract: This article examines exoneration and exculpation provisions in English and US style trust deeds and considers the extent to which the law applicable to these is the same and how it may differ. The question is how far a trustee may go to exclude liability for breach of duty of care and the legal basis for this. It then examines what perhaps should be the initial question, namely, the extent to which a deed of trust can remove such duties so that no trustee liability arises in the first place. The question is the extent to which removal of duties of care is permissible.